Peran Badan Usaha Milik Desa (Bumdes) Bersama “Bangkit Mandiri Sejahtera” dalam Penguatan Ekonomi Rakyat di Desa Nita, Kecamatan Nita, Kabupaten Sikka, NTT - Pariangu, Umbu TW; Bhala, Theresia Yuliana (Kybernology : Journal of Government Studies, 2024)
BUMDEs Bersama Bangkit Mandiri Sejahtera (BMS) located in Nita Village, Nita District, Maumere Regency operates in the following types of business: capital-based credit for agricultural businesses, weaving businesses, educational needs and savings and loans, trading (ikat woven materials, agricultural production facilities, necessities daily staples, building materials, office stationery); market management services (regional market management). The aim of this research is to determine the role of BUMDes BMS in strengthening the economy of village residents. The research method used in this research is qualitative descriptive research with data collection techniques, namely observation participation in various BUMDes BMS activities. In order to obtain coherent data, in-depth interviews were conducted with BUMDes managers, village government and community members. Based on research results, BUMDes BMS has provided economic strengthening for village people based on developing agricultural potential (providing agricultural production facilities) and ikat weaving raw materials, in addition to routinely providing loan services for residents and serving the basic needs of village residents. However, one of the problems experienced is in the savings and loans sector, in the form of bad credit or slow capital turnover, which makes the management of BUMDes ineffective. Apart from that, BUMDes has not been able to expand strategic types of business based on the prospects and potential that exist in the village. In the future, it is necessary to strengthen the management skills of BUMDes employees in managing strategic economic assets in the village well. In addition, it is necessary to expand businesses based on community needs and village development, so that strengthening the people's economy can be realized optimally.